Dampak Kebijakan Ekspor Bijih Nikel Indonesia Terhadap Ekspor Nikel Olahan - Ananda, Putri; Tri Wahyuni, Ribut Nurul (Politeknik Statistika STIS, 2024)
Indonesia, the world's largest nickel supplier, has implemented three policies regarding nickel ore exports in order to boost the export of refined nickel, which has a higher added value (nickel downstream). The objective of this study is to assess the impact of these policies on Indonesian processed nickel export volumes from January 2012 to December 2023. Interrupted time series analysis is the methodology used. The test results indicate that the policy of prohibiting nickel ore exports in 2014 has the potential to decrease the volume of Indonesian processed nickel exports in the first month of its implementation. The implementation of the relaxation policy for exports of nickel ore grade <1.7% also contributed to the decline in the trend in the volume of Indonesian processed nickel exports from 2017 to 2019. In the interim, the policy of prohibiting the export of nickel ore with a grade of less than 1.7%, which was implemented on January 1, 2020, has the potential to elevate the volume of Indonesian processed nickel exports. Therefore, implementing a prohibition on the export of nickel ore with a grade of less than 1.7% since 2020 can strengthen the nickel downstream program, as it has been shown to increase Indonesia's exports of processed nickel. This phenomenon arises as nickel smelters enhance their capacity to process nickel ore.